Adaptive Whisking in Mice - Chakrabarti, Shubhodeep; Nambiar, Jithin; Schwarz, Cornelius (Frontiers in Systems Neuroscience, 2022)
Rodents generate rhythmic whisking movements to explore their environment. Whisking trajectories, for one, appear as a fixed pattern of whisk cycles at 5-10 Hz driven by a brainstem central pattern generator. On the other hand, whisking behavior is thought to be versatile, and adaptable to behavioral goals. To begin to systematically investigate such behavioral adaptation, we established a whisking task, in which mice altered the trajectories of whisking in goal-oriented fashion to gain rewards. Mice were trained to set the whisker to a defined starting position, and generate a protraction movement across a virtual target (no touch related tactile feedback). By ramping up target distance based on reward history, we observed that mice are able to generate highly specific whisking patterns suited to keep reward probability constant. On a sensorimotor level the behavioral adaptation was realized by adjusting whisker kinematics: more distant locations were targeted using higher velocities (i.e. pointing to longer force generation), rather than by generating higher acceleration (i.e. pointing to stronger forces). We tested the paradigm’s suitability of tracking subtle alteration in whisking motor commands using small lesions in rhythmic whisking (RW) subfield whisking-related of primary motor cortex. Small contralateral RW lesions generated deterioration of whisking kinematics with a latency of 12 days post-lesion, a change that was readily discriminated from changes in behavioral adaptation by the paradigm.